+0  
 
0
69
1
avatar

If xy(x + y) = 1, then find \(\dfrac{1}{x^3 y^3} - x^3 - y^3\)

 Jan 10, 2020
 #1
avatar+109739 
+1

Note that  we can  write

  

    1                                             1

______  - x^3 - y^3       as     ________  - ( x ^3 + y^3)     

x^3y^3                                      x^3y^3

 

xy ( x + y)  =  1       ⇒  x^2y + y^2x  = 1   ⇒  [ 3x^2y + 3y^2x ] = 3

 

x + y  =  1 / [xy]           cube both sides

 

x^3  + 3x^2y + 3y^2x  + y^3  =   1 / [x^3y^3 ]

 

x^3  + [ 3x^2y + 3y^2x ] + y^3  =  1 / {x^3y^3]

 

x^3 +   3   + y^3    =  1 / [ x^3y^3]

 

3  =   1 / [ x^3y^3 ] - (x^3 + y^3]

 

 

cool cool cool

 Jan 10, 2020

24 Online Users

avatar
avatar